ANALISA PENGARUH PEMILIHAN TEKNOLOGI TERHADAP STRATEGI KOMPETITIF PADA SEJUMLAH PERUSAHAAN INDUSTRI KOMPONEN ELEKTRONIKA DI BATAM - Suwarno, Suwarno (Computer Based Information System Journal, 2020)
Technology has become a major part in all areas of life, covering the lives of individuals and communities. Especially in the city of Batam, as an industrial city ranging from the electronics industry to shipyards. In Batam city, there are 129 electronics component industry companies. Technological developments continue to change, therefore electronics component industry companies always adopt the latest technology to support business processes. The choice of technology has become part of a competitive strategy that can keep the company sustain. In the selection of this technology, there are four important variables can be utilized by the company in a manner, they are: innovation, research and development, technology resources, technology exploitation and investment. As the results of the study, these four variables significantly influence 66.9% of competitive strategy in a number of electronics companies in the city of Batam.